Plan de negocio para la creación de un motel en el barrio Tapalán vía Culahuango, en la ciudad de Latacunga en el año 2014 - Bunchi Lema, Mayra Elizabeth (2015)
The current project "Business Plan for the creation of a motel in the Tapalán neighborhood Culahuango route in Latacunga city in the year 2014", has as aim to demonstrate the feasibility of creating through the systematic development of a business plan that offers a new alternative of tourist accommodation for that sector, ,because the currently problem is the lack of tourist accommodation that can contribute to the development of the economy and tourism in order to improve the economy of that population and economic conditions of employees and investors. For that the best option that has been determined to give a possible solution to the problem raised in that place, according to its location, economic conditions, culture, customs of the people is building a motel for those people who are seeking a short stay or visit the sector. With regard to research and study of the thesis theme is disclosed that by collecting methodical data used as techniques of observation and surveys of the population, was determined and verified the feasibility of their implementation, also important data such as the amount of unsatisfied demand was obtained in which a percentage of 74% of persons or potential customers to, who the service may be offered according to the installed capacity of the project which are going to be implemented in the agreed year, was determined.